Research on agri-environmental technology efficiency——take Jilin Province in China as an example - He Xu; Shuai Liu (Heliyon, 2024)
From the perspective of the world agricultural development law, agricultural economic development and ecological environmental protection usually fall into a dichotomy paradox, according to the history of agricultural development in developed countries, they also experienced the rapid development of agriculture led to the destruction of the agro-ecological environment, which has become a key element hindering the sustainability of agriculture. Subsequently, developed countries rely on modern technology to achieve the transition from traditional agriculture to modern agriculture, crossing the paradoxical trap of economic development and ecological construction. At the present stage, China also shows the sharp contradiction between agricultural development and ecological construction, the traditional agricultural production methods of agricultural output has basically reached the limit, however, the established production methods of the ecological environment caused by the negative effects of the more and more serious, so that the agricultural environmental technology efficiency is not optimistic, so there is an urgent need to have a clear understanding of the main grain-producing areas of China's agricultural environmental technology efficiency and the factors affecting it. As an important grain producing area in China, Jilin Province's agricultural development level is in the forefront of the country, and it is also facing the contradiction between agricultural development and ecological environmental protection at the present stage. In order to realize the green transformation of agriculture and improve the technical efficiency of agricultural environment, it is necessary to rely on the optimisation of multi-dimensional factors such as technology and system. The study of agricultural environmental technical efficiency in Jilin Province has important theoretical significance and practical value for guiding other agricultural areas to realize the green transformation of production mode.